The Rhadamanthys Quality of Context Architecture - Brauner Filho, Hélio Carlos; Geyer, Claudio Fernando Resin (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP), 2017)
With the rising number of Internet of Things devices and context providers, the need for sorting and selecting them according to user requirements and to the quality of sensed information becomes prevalent. Thus, this paper presents the Rhadamanthys architecture, designed to fulfill this requirement using Quality of Context information for both ranking and selection. Individual Quality of Context criteria as defined in the literature are evaluated for each available provider and used in formulae to obtain a single score that enables ranking and allows selection.